1999
DOI: 10.1095/biolreprod60.4.805
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Effect of Repeated Equine Chorionic Gonadotropin Treatment on Subsequent Fertility in Alpine Goats Is Due to a Humoral Immune Response Involving the Major Histocompatibility Complex1

Abstract: In dairy goats, the use of eCG as a convenient hormone for the induction of ovulation is necessary for out-of-season breeding and artificial insemination. However, repeated eCG treatments are followed by decreased fertility in goats inseminated at a fixed time after treatment. In this report, we show the presence of anti-eCG antibodies in plasma of treated goats. A 500 IU eCG injection induces a humoral response, with variable concentrations of anti-eCG antibody being produced in individual goats. The analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
59
2
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 33 publications
8
59
2
8
Order By: Relevance
“…Indeed, in the present experiment, only 15% and 39% of the does receiving 8 or 25 IU, respectively, developed a significant immune reaction just before the 11th injection. Recently, Roy et al (1999) demonstrated that the negative effect of repeated eCG treatments on subsequent fertility in Alpine goats was due to a humoral immune response involving the major histocompatibility complex. Unfortunately, we could not find any study on genetic sensibility to eCG realized in the rabbit species.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the present experiment, only 15% and 39% of the does receiving 8 or 25 IU, respectively, developed a significant immune reaction just before the 11th injection. Recently, Roy et al (1999) demonstrated that the negative effect of repeated eCG treatments on subsequent fertility in Alpine goats was due to a humoral immune response involving the major histocompatibility complex. Unfortunately, we could not find any study on genetic sensibility to eCG realized in the rabbit species.…”
Section: Discussionmentioning
confidence: 99%
“…eCG's effect after repetitive use (revised by DRION et al, 1998;ROY et al, 1999a;DRION et al, 2001). the positive effect of eCG on follicle development has not been completely determined.…”
Section: Discussionmentioning
confidence: 99%
“…the eCG administration can increase the concentration of anti-eCG antibodies after the first use (ROY et al, 1999b;MaNtOVaNI, 2010) and some studies have reported an additive effect of subsequent treatments (ROY et al, 1999a;DRION et al, 2001). Furthermore, most studies have concluded that there is an animal individuality to the immune response against eCG (DRION et al, 2001;MaNtOVaNI, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations